Detection of irradiated rose tea based on electron spin resonance (ESR) technology - ZHAO Xiao-jun; FU Jun-jie; TAN Yuan-yuan; WANG Zhi-ping (浙江大学学报. 农业与生命科学版)
The characteristic of ESR spectrum of rose tea irradiated by 60Co-γ ray at different doses was studied. The relationship of ESR signal intensity with irradiation doses, and storage time with peak value, respectively, was also discussed. The result showed that the ESR spectrums were obviously different at the presence or absence of irradiation. The ESR signal intensity increased with the increasing of irradiation dose, but decreased with the expanding of storage time with a linear correlation. The ESR signal intensity was weakened gradually during the store at room temperature for 120 days, but the ESR signal could be still detected, which could be used to easily distinguish irradiated rose tea samples from those unirradiated.